Establishing a 501(c)(3) Nonprofit Organization: An Overview - Jacqueline Phillips; Jorge H. Ruiz-Menjivar; Jennifer A. Jones; Julianne Shoup (EDIS)
This new 3-page document provides an overview of the process to establish a 501(c)(3) nonprofit organization and also discusses eligibility criteria and filing requirements. Written by Jacqueline Phillips, Jorge Ruiz-Menjivar, Jennifer A. Jones, and Julianne Shoup, and published by the UF/IFAS Department of Family, Youth and Community Sciences, April 2019. http://edis.ifas.ufl.edu/fy1481